The fundamentals of visualization, modeling, and graphics for engineering design - Lieu, Dennis Kenmon; Sorby, Sheryl Ann (Delmar Cengage Learning, 2009)
A new book for a new generation of engineering professionals, Visualization, Modeling, and Graphics for Engineering Design was written from the ground up to take a brand-new approach to graphic communication within the context of engineering design and creativity. With a blend of modern and traditional topics, this text recognizes how computer modeling techniques have changed the engineering design process. From this new perspective, the text is able to focus on the evolved design process, including the critical phases of creative thinking, product ideation, and advanced analysis techniques. Focusing on design and design communication rather than drafting techniques and standards, it goes beyond the "what" to explain the "why" of engineering graphics.